Collective Responsibility Redefining What Falls Between the Cracks for School Reform - Whalan, Frances; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
How to achieve school reform and organisational change has been a subject of much inquiry and interest by educators, education systems and academics. This volume advances both conceptual and methodological knowledge in understanding the cultural changes required at the school level to develop teachers$1 (Bcollective responsibility for student learning. The concept of teachers$1 (Bcollective responsibility is both intriguing and elusive as it traverses both sociological and psychological aspects of teaching. Five major but interconnected discourses: professional community; professional development; relational trust; accountability; and efficacy map the terrain of this complex phenomenon. Results reported in this volume provide clear evidence that collective responsibility is positively correlated the coherence between professional learning programs and the school$1 (Bs learning goals, teachers$1 (Bcommitment to enact those shared goals and teacher-to-teacher trust. In addition, teachers$1 (Bcollective struggle to address pressing issues for teaching and learning, and pedagogical leadership, when embedded in the organisational capacity of a school, form a complex and dynamic set of factors influencing the development of collective responsibility. Drawing together these important findings surfaces a need to rethink how schools, education systems and academics pay attention to what falls between the cracks for school reform. This book addresses aspects of school culture that guide the choices in the development of teachers$1 (Bcollective responsibility. Professional development, collective struggle, professional community, relational trust and pedagogical leadership as elements of school culture and organisational reform are modelled as a continuum of micro-political conditions interacting at the school level. This model offers new insights into the complexity of collective responsibility as a multi-dimensional phenomenon and is a useful guide to organisational change for school and system leaders and academics whose research interests are focused on the how of organisational change.s
Keywords: Education; Education; Education (general).